Equal pay for equal work - Labour Party report, 1930 (1930)
1930 1918-1939 "Equal pay for equal work - Labour Party report, 1930" [EP0090], 1930 This Labour Party pamphlet contains two reports on equal pay and on a domestic workers' charter, prepared by the Standing Joint Committee of Industrial Women's Organisations for the National Conference of Labour Women, held in London, June 3-5, 1930. The four main recommendations in the equal pay report are improved trade union organisation of women, equality in the public sector, extension of the trade boards system and abolition of the marriage bar.